2017
DOI: 10.21037/jtd.2017.08.17
|View full text |Cite
|
Sign up to set email alerts
|

Lung densitometry: why, how and when

Abstract: Lung densitometry assesses with computed tomography (CT) the X-ray attenuation of the pulmonary tissue which reflects both the degree of inflation and the structural lung abnormalities implying decreased attenuation, as in emphysema and cystic diseases, or increased attenuation, as in fibrosis. and with pulmonary fibrosis. It has also been applied to assess prevalence of smoking-related emphysema and to monitor progression of smoking-related emphysema, alpha1 antitrypsin deficiency emphysema, and pulmonary fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 132 publications
1
78
0
3
Order By: Relevance
“…The recently introduced densitometric- and histogram-based analysis of CT images provides data on mean lung attenuation, skewness, and kurtosis. These parameters have been reported to show associations with parameters of pulmonary function and disease progression in various lung diseases [ 56 ]. In addition, some objective CT measurements have been found to be useful for the long-term monitoring of patients with emphysematous and fibrotic lung disease [ 25 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently introduced densitometric- and histogram-based analysis of CT images provides data on mean lung attenuation, skewness, and kurtosis. These parameters have been reported to show associations with parameters of pulmonary function and disease progression in various lung diseases [ 56 ]. In addition, some objective CT measurements have been found to be useful for the long-term monitoring of patients with emphysematous and fibrotic lung disease [ 25 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, the inner spaces of honeycombing and airspace enlargement associated with fibrosis might have been assessed as LAA. However, reports on the measurement of honeycombing with a background of fibrotic lesions are rare, and methodologies for distinguishing between honeycombing and LAA have not been elucidated [ 56 ]. Additionally, pulmonary vessels were partially included in the HAA values.…”
Section: Discussionmentioning
confidence: 99%
“…21,49,50,[52][53][54][55][56][57] Disease can impact lung density, 58 for example, decreased lung attenuation typically occurs in emphysema or cystic lung diseases, whereas focal increased attenuation occurs in fibrosis. 59 Often, disease can lead to variable lung attenuation, as shown by example in Fig. 6.…”
Section: Challenges In the Lungmentioning
confidence: 99%
“…Additionally, research has shown that the visual evaluation of CT scans has low reproducibility [ 48 ]. However, the use of densitometric evaluation improves the utility of CT scans in diagnosing chronic lung disease [ 49 ].…”
Section: Introductionmentioning
confidence: 99%